Tax Planning Strategies for Tax Saving at PT Ramayana Lestari Sentosa, Tbk - Hendy Rizki Junyes; Ida Farida Adi Prawira; Memen Kustiawan (Universitas Muhammadiyah Makassar, 2025)
This study aims to analyze tax planning strategies to minimize the corporate income tax expense at PT Ramayana Lestari Sentosa, Tbk by utilizing legal tax deductions according to Indonesian tax regulations. The research employs a qualitative descriptive approach, using the company’s annual financial statements from 2022 and 2023 as the primary data source. Through detailed analysis of the income statements and fiscal reconciliation reports, the study identifies deductible expenses that can be strategically allocated to reduce taxable income and, consequently, tax expenses. The findings reveal that reallocating certain costs—such as donations, entertainment, employee welfare, research and development, scholarships, internships, and training—into tax-deductible categories effectively reduces the tax expense. Specifically, the company was able to lower its income tax expense by approximately IDR 2.826 billion in 2022 and IDR 1.433 billion in 2023. These tax savings were achieved by optimizing cost allocations in compliance with prevailing tax laws, including Indonesian Law No. 36 of 2008, which allows deductions for costs related to social infrastructure and human resource development. The study highlights the importance of tax planning as a legal method for companies to manage tax liabilities without violating tax regulations. This research contributes practical insights for corporate tax management, demonstrating that strategic allocation of deductible expenses can significantly impact the company’s financial performance by reducing tax burdens. Ultimately, effective tax planning enhances corporate efficiency and compliance, supporting sustainable business growth.